Health and Health Care In Developing Countries : Sociological Perspectives - Gallagher, Eugene B.; Conrad, Peter, 1945- (Book collections on Project MUSE., 1993)
In this seminal collection of articles on health care in the Third World, sociological perspectives are applied to medical issues in revealing ways. Fourteen essays (all but two of which are original to this volume) examine the social production of health, disease, and systems of care throughout the developing world. The volume covers a range of areas - central Africa, Nigeria, Singapore, Taiwan, Indonesia, Nepal, China, United Arab Emirates, Oman, and Mexico - and a broad scope of topics, from emergency care, the AIDS epidemic, and women's health care, to public health programs and national health care policies. Contributors address the central question of whether health systems in developing areas should emphasize the role of clinical medicine and individual physicians or community and preventive medical resources. The major health problems faced by these societies - inadequate sanitation, infectious disease, high infant-child mortality, and a lack of family planning - indicate the greater need for health educators and public health workers despite many poor nations' desire for Western doctors. Other topics that are examined include the process of seeking medical aid; the relationship between traditional and modern medicines; medical education, hospital care, and communication between doctors and patients in developing countries; and the relevance and application of sociology in Third World settings. This volume seeks to draw attention to the significance of medical sociology for understanding Third World health problems and to show how examining developing societies may necessitate reframing or modifying some Western sociological notions. In addition, these essays stretch the boundaries of medical sociology to include Third World issues.